RI 7975 Detection and Delineation of Faults by Surface Resistivity Measurements - Schwartzwalder Mine, Jefferson County, Colo. - Robert Lee Stahl (The National Institute for Occupational Safety and Health (NIOSH), 1974)
Comprehensive field tests were made by the Bureau of Mines at the Schwartzwalder mine near Golden, Colo., to determine whether surface geophysical techniques could be used to detect and delineate faults in uranium deposits. The tests included seismic refraction, magnetometer, electrical resistivity, airborne infrared thermal scanning, and airborne photography. Of the several geophysical techniques tested in the field, horizontal resistivity profiling with electrode spacings in the range of 10 to 15 feet was most diagnostic of faults. The method is quick, inexpensive, and accurate and can be easily used by mining company personnel to detect and delineate faults.